The chick embryo as an expanding experimental model for cancer and cardiovascular research - Kain, Kristin H. (2013)
A long and productive history in biomedical research defines the chick as a model for human biology. Fundamental discoveries, including the description of directional circulation propelled by the heart and the link between oncogenes and the formation of cancer, indicate its utility in cardiac biology and cancer. Despite the more recent arrival of several vertebrate and invertebrate animal models during the last century, the chick embryo remains a commonly used model for vertebrate biology and provides a tractable biological template. With new molecular and genetic tools applied to the avian genome the chick embryo is accelerating the discovery of normal development and elusive disease processes. Moreover, progress in imaging and chick culture technologies is advancing real-time visualization of dynamic biological events, such as tissue morphogenesis, angiogenesis and cancer metastasis. A rich background of information, coupled with new technologies and relative ease of maintenance suggest an expanding utility for the chick embryo in cardiac biology and cancer research.